Study on osmotic stress tolerance in promising durum wheat genotypes using drought stress indices - Moayedi, A.A.; Boyce, A.N.; Barakbah, S.S. (2009)
One way to overcome the negative effects of water stress on crop production is the development of drought tolerant cultivars. In the present study we have attempted to quantify the drought tolerance of several durum wheat genotypes using stress indices. The study was laid out in factorial experiments based on a completely randomized design (CRD) with three replications and two factors. Twenty promising durum wheat genotypes were germinated under four (0.0, -0.3, -0.6 3 and -0.9 MPa) osmotic stresses conditions produced using different concentrations of Polyethylene glycol (PEG 6000) at 20Â°C. The results showed that the effect of osmotic stress on the germination stress index (GSI) was highly significant (P<0.01) and increasing osmotic stress significantly decreased the GSI values. In terms of the germination stress tolerance index (GSTI), a comparison of the different genotype responses to osmotic stress based on root length, root dry weight and seedling dry weight, showed that genotype number 4 (RASCON39/TILO1) was most tolerant under low osmotic stress (-0.3 MPa) while G10 (RASCON37/BEJAH7) exhibited the highest GSTI under severe osmotic stress (-0.9 MPa) conditions. On the other hand genotypes G17 (GARAVITO3/RASCON37//GREEN8) and G7 (HAIOU17/GREEN38) showed the lowest GSTI under osmotic stress conditions. These results indicate that genotypes number 10 and 4 may be suitable for planting in arid and semi-arid areas that are subjected to severe or mild drought stresses.